2013
DOI: 10.1080/02687038.2013.845739
|View full text |Cite
|
Sign up to set email alerts
|

Semantic feature analysis: Application to confrontation naming of actions in aphasia

Abstract: Background: Despite advances in the development and testing of therapies for verb retrieval impairments in aphasia, generalisation effects of treatment remain a challenge. Semantic Feature Analysis (SFA) is a word retrieval treatment that has been reported to result in generalised responding to untrained object names with persons with aphasia. The theorised therapeutic mechanisms of SFA appeared to be appropriate for facilitating retrieval of trained and untrained action names. Aims: This investigation was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…Nine studies investigated SFA with confrontation naming of nouns (Boyle, 2004;Boyle & Coelho 1995;Coelho, McHugh & Boyle, 2000;Davis & Stanton, 2005;DeLong, Nessler, Wright, & Wambaugh, 2015;Hashimoto & Frome, 2011;Massaro & Tompkins, 1994;Mehta & Isaki, 2016;Rider, Wright, Marshall, & Page, 2008). Two studies examined SFA with confrontation naming of verbs (Wambaugh & Ferguson, 2007;Wambaugh, Mauszycki, &Wright, 2014) and a further two tested SFA with confrontation naming of nouns and verbs (Kristensson, Behrns, & Saldert, 2015;Marcotte & Ansaldo, 2010). Kristensson's study additionally explored everyday conversation and functional communication outcomes.…”
Section: Study Selectionmentioning
confidence: 99%
“…Nine studies investigated SFA with confrontation naming of nouns (Boyle, 2004;Boyle & Coelho 1995;Coelho, McHugh & Boyle, 2000;Davis & Stanton, 2005;DeLong, Nessler, Wright, & Wambaugh, 2015;Hashimoto & Frome, 2011;Massaro & Tompkins, 1994;Mehta & Isaki, 2016;Rider, Wright, Marshall, & Page, 2008). Two studies examined SFA with confrontation naming of verbs (Wambaugh & Ferguson, 2007;Wambaugh, Mauszycki, &Wright, 2014) and a further two tested SFA with confrontation naming of nouns and verbs (Kristensson, Behrns, & Saldert, 2015;Marcotte & Ansaldo, 2010). Kristensson's study additionally explored everyday conversation and functional communication outcomes.…”
Section: Study Selectionmentioning
confidence: 99%
“…So for example, studies have attempted to adapt SFA treatment (applied initially to nouns) for verbs by adapting the features generated during treatment to be more appropriate (or active) for verbs (e.g. Wambaugh Mauszycki & Wright, 2014;Wambaugh & Ferguson, 2007). In SFA treatment, the likely active ingredient of treatment is the generation of semantic features for a target word (see Gravier et al, 2018).…”
Section: Verb Retrieval Deficits In Aphasia: Theory and Therapymentioning
confidence: 99%
“…Ten studies reported the minimum and maximum length of sessions as well as the number of sessions which allowed the estimation of the minimum and maximum total amount of treatment (Bonifazi et al,;Boo & Rose, 2011;Conroy, Sage & Lambon-Ralph, 2009 a, b and c;Marangolo et al, 2010;McCann & Doleman, 2011;McNeil et al, 1998;Routhier, Bier & Macoir, 2016). Wambaugh and colleagues reported a series of studies where the amount of treatment was dependent on reaching a predetermined performance criterion, meaning amount of treatment given differed (Wambaugh et al, 2014;Wambaugh & Ferguson, 2007;Wambaugh, Cameron, Kalinyak-Fliszar, Nessler & Wright, 2004;Wambaugh, Doyle, Martinez, & Kalinyak-Fliszar, 2002). Takizawa, Nishida, Ikemoto, & Kurauchi (2015) reported huge variation in the duration and intensity of treatment given in their clinical study: one to five 40-minute sessions per week over a span of 2-8 months.…”
Section: What Is the Fidelity Of The Research In Terms Of Treatment Dmentioning
confidence: 99%
“…Several researchers have applied SFA to verb retrieval. 45,46,49,50 In these studies, the semantic feature categories used during treatment were modified from the ones used for object naming to make them more appropriate for generating semantic features for actions, but the other aspects of treatment were the same. The feature categories used were subject, purpose of action, part of body or tool used to carry out the action, description, usual location, and association.…”
Section: Semantic Feature Analysis For Actionsmentioning
confidence: 99%